Text book of soil mechanics and foundation engineering: geotechnical engineering series - Murthy, V.N.S (CBS Pub., 2016)
Text book of soil mechanics and foundation engineering: geotechnical engineering series / Murthy, V.N.S.. -- Kolkata: CBS Pub., 2016 624.15136 M984 No. of Copies : 1